ASSESSMENT OF CONDITIONS FOR STUDENTS’ CAREER COMPETENCIES TRAINING EFFECTIVENESS - Rosinaitė, Vikinta (Acta Paedagogica Vilnensia, 2009)
Career education stimulates consciousness and independence in labour market participants and promotes reduction of social exclusion. Career education in the Western World is getting more and more important. Unfortunately in Lithuanian educational system training of career competencies is very poor. The purpose of this article is to assess conditions for the first systemic students’ career education program effectiveness in Lithuania.The purpose of the first systemic students’ career education program in Lithuania was to train career development competencies. Hence the change of these competencies should show the most, if the training was effective. All participants of this training have improved their career competencies, so it proves that this career competencies education program was successful. The article also assessed these conditions for students’ career competencies training effectiveness: organization of career competencies training, ability of career consultants to educate students’ career competencies during training, students’ personal effort during learning process, course materials (course books and practical exercises). Recommendations related to conditions for career competencies training effectiveness are presented in this article according to the results of this study.
Keywords: personal career; career education; career competencies; training of career competencies; training effectiveness